Effects of material and infill density towards adjustable headrest orthosis development based on 3D printing technology / Madya Mastika Ahmad - Ahmad, Madya Mastika (2020)
In recent years, there has been a number of noteworthy improvements and considerable advances s in the medical management of cerebral palsy (CP). Children with spastic or dyskinetic CP struggle to stand still and they spend most of their time seated, spending most of their time in a wheelchair. Therefore, a suitable headrest to maximize independence and functionality in sitting position, is a good addition. This study aims to analyze the effects of material properties and infill density in selected 3D printing material in an adjustable headrest for total body involvement in CP children as well as to determine the material used to fabricate the adjustable headrest in addition to fabricate the adjustable headrest using the chosen material in a 3D printer. The headrest is designed as a curved headrest with lateral support by means of three-point lateral control and affixed with a head strap for temporal support. It is subjected for use with children with age range from seven to nine years and limited to a five types of 3D printing materials namely ABS (Acrylonitrile Butadiene Styrene), Nylon (Polyamide), PETG (Polyethylene Terephthalate), PC (Polycarbonate) and PLA (Polylactic Acid). A Computer Aided Design (CAD) software is utilised in the design process and subsequently the final design is analysed using the Finite Element Model (FEA). A selection of 20%, 40%, 60% and 80% of infill density is applied as well as increment of pressure magnitudes of 5 kPa, 10 kPa, 15 kPa, 20 kPa and 25 kPa to predict the safety of the product at higher impact load. PLA is selected as the final material as it has the optimum value in stress, deformation and safety factor parameters.